A Direct Xanthate-Based Route to γ-Thiolactones - Simonet-Davin, Raphaël; Zard, Samir Z. (Synlett, 2018)
The first examples of direct synthesis of γ-thiolactones by addition of a thiolactone-based radical are described. Mono- and bis-γ-thiolactones can be obtained by a dilauroyl peroxide initiated addition of thiolactone xanthate to various alkenes and α,ω-dienes. The process is modular and exhibits a high functional group tolerance.
Keywords: xanthates; alkenes; radical addition; thiolactones; polymers